2016
DOI: 10.1002/2016ef000377
|View full text |Cite
|
Sign up to set email alerts
|

Crop yield changes induced by emissions of individual climate‐altering pollutants

Abstract: Climate change damages agriculture, causing deteriorating food security and increased malnutrition. Many studies have examined the role of distinct physical processes, but impacts have not been previously attributed to individual pollutants. Using a simple model incorporating process-level results from detailed models, here I show that although carbon dioxide (CO 2 ) is the largest driver of climate change, other drivers appear to dominate agricultural yield changes. I calculate that anthropogenic emissions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…In the tropics, new agricultural land has come at the expense of rainforests, savanna, and other ecosystems, and future expansion will clear ever more (Gibbs et al 2010). There is also a feedback in which emissions of methane and nitrous oxide from agriculture lead to crop yield reductions, so that agricultural expansion can require further expansion (Shindell 2016). …”
Section: Land-system Changementioning
confidence: 99%
“…In the tropics, new agricultural land has come at the expense of rainforests, savanna, and other ecosystems, and future expansion will clear ever more (Gibbs et al 2010). There is also a feedback in which emissions of methane and nitrous oxide from agriculture lead to crop yield reductions, so that agricultural expansion can require further expansion (Shindell 2016). …”
Section: Land-system Changementioning
confidence: 99%
“…Crop responses to temperature are regionally varying with values in units of percent yield per degree warming of (temperate regions and tropical regions): maize (−2.4, −3.4), wheat (−2.4, −13.8), and rice (−3.2, −2.0) based on the meta‐analysis (Challinor et al, ). This compares with the uniform global mean value of −4.9% yield change per degree for all crops in Shindell () based on this same meta‐analysis. For consistency with the underlying meta‐analysis, we define regions as follows: Tropical regions are those from 30°S to 30°N except for longitudes 20°W to 60°E (North Africa and the Middle East) where we use 20°S–20°N for all crops.…”
Section: Modelingmentioning
confidence: 68%
“…As such, extant research does not provide a clear indication of the impact of the individual emissions that drive, in many cases, both climate change and ozone concentrations. An initial study to quantify the effects of individual pollutants on agriculture was performed recently, examining global aggregate results only (Shindell, ). Here we build on that work, now examining the spatial distribution of the crop yield impacts of all major pollutants that occur via the physiological (CO 2 and ozone exposure) and climate‐related (temperature and precipitation) impacts of emissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FACE and chamber experiments that combine elevated CO 2 with additional treatments suggest that crop yields will either not change or will decrease in response to the combination of future CO 2 , temperature, N deposition, and O 3 (Cai et al, ; Cardoso‐Vilhena et al, ; Feng et al, ; Long et al, ; Rudorff et al, ; Ruiz‐Vera et al, ). Similarly, using an analytical model, Shindell () found that crop yields may decrease up to 25% relative to a lower‐emission (RCP2.6) scenario, largely due to the negative impacts of climate. Our results project only a 5% global increase in crop yields by the end of the 21st century under the combination of RCP8.5 forcings (Figure ), further suggesting that the increased food demand in the future, an estimated 65% by 2100 (Bodirsky et al, ), is not likely to be met under the RCP8.5 future scenario without agricultural expansion and advances in agronomic techniques that intensify agricultural production and buffer negative climate impacts.…”
Section: Discussionmentioning
confidence: 99%